2019
DOI: 10.1371/journal.pone.0215192
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Th17.1 cells as candidate for the prediction of therapeutic response to abatacept in patients with rheumatoid arthritis: An exploratory research

Abstract: T-helper (Th)17.1 cells exhibit high pathogenicity in inflammatory diseases. This study aimed to identify the changes in the proportions of Th subsets, including Th17.1, which are associated with abatacept treatment response in Japanese patients with rheumatoid arthritis. On the basis of the results, we assessed whether Th17.1 is a potential cellular biomarker. Multicolor flow cytometry was used to determine the circulating Th subsets among CD4+ T lymphocytes in 40 patients with rheumatoid arthritis before aba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 49 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…We found that Th17.1-like cells were significantly increased within the total Th17-like subset in severe COVID-19 compared to those in moderate COVID-19 and in the HD. It has been shown that Th17.1 cells produce cytokines, including IL-17A, GM-CSF, IFN-γ, and TNF-α, which are associated with inflammatory conditions [ 59 , 60 ] and influence different cell types at the site of infection, including tissue macrophages, epithelial cells, and endothelial cells by inducing pro-inflammatory mediator expression and promoting neutrophil recruitment [ 61 ]. Thus, Th17.1 and their cytokines could be involved in secondary tissue damage during severe SARS-CoV-2 infection, but the role of Th17 cells in COVID-19 pathogenesis remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…We found that Th17.1-like cells were significantly increased within the total Th17-like subset in severe COVID-19 compared to those in moderate COVID-19 and in the HD. It has been shown that Th17.1 cells produce cytokines, including IL-17A, GM-CSF, IFN-γ, and TNF-α, which are associated with inflammatory conditions [ 59 , 60 ] and influence different cell types at the site of infection, including tissue macrophages, epithelial cells, and endothelial cells by inducing pro-inflammatory mediator expression and promoting neutrophil recruitment [ 61 ]. Thus, Th17.1 and their cytokines could be involved in secondary tissue damage during severe SARS-CoV-2 infection, but the role of Th17 cells in COVID-19 pathogenesis remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Along this line, CTLA4-Ig treatment was found to significantly reduce T-cell repertoire restriction [ 24 ] and to significantly increase peripheral blood-derived CD4 pos CD25 pos FoxP3 pos regulatory T lymphocyte rate in RA patients together with their apoptosis [ 25 ]. However, conflicting data were produced about the relation between peripheral blood-derived activated Th17 cells and CTLA4-Ig induced disease remission in RA patients [ 26 , 27 ], while peripheral blood-derived activated Treg cells before treatment were found to be significantly higher in RA patients achieving disease remission with CTLA4-Ig [ 26 ]. In our study, we found that CTLA4-Ig treatment significantly reduces the rates of peripheral blood-derived CD4 pos CD25 pos FoxP3 pos cells in RA patients regardless of their disease duration.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic Th17 cells are considered to be involved in RA pathogenesis. Targeting pTh17 cells or associated molecules may be a potential strategy for clinical diagnosis, treatment, and prognosis of RA ( 24 , 25 ). In our previous study, we observed that transcription factor YY1 was overexpressed in RA patients and promoted Th17 cell polarization by regulating IL-6 ( 16 ).…”
Section: Discussionmentioning
confidence: 99%